Child risk assessment of selected metal(loid)s from urban soils using in vitro UBM procedure - Szymon Łucjan Różański (Elsevier, 2021)
In city agglomerations significant pollution results from fossil fuel combustion from heat and power plants, transportation, and boilers in households. In this context, pollution from recalcitrant, environmentally accumulative metal(loid)s can be a critical human health risk. In day-care centers, playgrounds, kindergartens, schools, and sport facility areas children may ingest significant quantities of potentially polluted soil and dust, increasing incidence of health disorders or diseases. The objective of this study was to assess the oral bioaccessibility and human health risk of As, Cd, Pb, Cr, Ni, Cu, and Zn from potentially polluted urban topsoils by applying gastrointestinal Unified Bioaccessibility Method (UBM) protocol. Total content of studied elements was relatively low and none of studied elements exceeded Polish legal limits for urban soils. According to the Enrichment Factor (EF), studied sites were characterized from minimal to significant degrees of soil pollution by analyzed metal(loid)s in the order: Pb > Zn > Cu > Cd > As > Ni > Cr. Concentrations of the metal(loid)s in bioaccessible phases were varied, and higher for gastric than gastrointestinal bioaccessibility. Metal(loid) bioaccessibility in soils of Bydgoszcz was highly correlated with total concentration. Almost no correlation was found between concentration of these phases and parameters like soil pH, texture, CaCO3, TOC, or CEC. A relationship did exist with landform where the lower positions had greater concentrations. These locations are those with the highest traffic density and operation of old coal heating systems leading to the highest deposition of airborne contaminants. Higher landscape positions are favored for new facilities in newer residential districts. Exposure and health risk from soil ingestion given normal ingestion scenario at any site investigated was very low. Non-carcinogenic and carcinogenic risk was identified only for soil pica behavior. Soil pica ingestion scenario might be considered for children with lapses of adult.